2005
DOI: 10.1103/physrevb.72.085326
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of 002 structure factors for electron scattering in strainedInxGa1xAs

Abstract: This work provides values of electron scattering 002 structure factors for In x Ga 1−x As as a function of the In concentration x = 0 to 1. These results allow accurate compositional analysis of pseudomorphically grown In x Ga 1−x As/ GaAs layers by transmission electron microscopy methods relying on the chemical sensitivity of the ͑002͒ beam. The calculations go beyond the limits of the isolated atom approximation, because they take into account charge redistribution effects between atomic sites in the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…The intensity of HAADF-STEM images was simulated using the STEMsim program [56] for varying Al-concentration y in dependence of the TEM lamella thickness. The static atomic displacement (SAD, [57][58][59]) in AlGaN can be neglected [55]. From the experimental image, an intensity profile along the growth direction was extracted.…”
Section: Al-concentration In Algan Layersmentioning
confidence: 99%
“…The intensity of HAADF-STEM images was simulated using the STEMsim program [56] for varying Al-concentration y in dependence of the TEM lamella thickness. The static atomic displacement (SAD, [57][58][59]) in AlGaN can be neglected [55]. From the experimental image, an intensity profile along the growth direction was extracted.…”
Section: Al-concentration In Algan Layersmentioning
confidence: 99%
“…As 2 source molecules were used. (002) amplitude is compared with (002) Fourier components calculated by the Bloch-wave method with structure factors which take also static atomic displacements into account [18]. Local thickness values of the TEM sample in regions with known composition, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For details, see Refs. [7,8]. In the latter report, we found that SAD from VFF are accurate to a few picometres, being less than mean thermal vibrational amplitudes.…”
Section: Modelling Bonding and Sad Effects On Electron Structure Factorsmentioning
confidence: 64%